PELANGGARAN DISIPLIN OLEH APARATUR PEMERINTAH NAGARI SILOKEK DALAM PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA (APB) NAGARI TAHUN ANGGARAN 2021 - Putri, Meysa Silvia; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Disciplinary violations in the form of corrupt practices carried out by several Nagari Silokek Government Apparatus in managing the Nagari APB, resulted in quite large losses, where the resulting state financial loss amounted to IDR 311,432,956.76,-. This research aims to describe the factors that influence disciplinary violations and factors that cause corruption committed by several Nagari Silokek Government Apparatus in the management of the Nagari APB for the 2021 fiscal year. The research location is in Nagari Silokek. This research uses Singodimedjo's Discipline Theory, which states that the factors that influence employee work discipline are the size of compensation, whether or not there is exemplary leadership in the organization, whether there are definite rules that can be used as a guide, the courage of leaders in making decisions, and whether there is supervision. leader. Apart from disciplinary theory, this research also uses Robert Klitgaard's CDMA theory, which states that corruption occurs due to several factors, including corruption, discretion (freedom/freedom of action), monopoly (monopoly), and accountability (accountability). This research uses a descriptive qualitative approach. The data collection techniques were carried out through interviews and document searches. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions or verification. The results of the research show that the factor influencing disciplinary violations by several Nagari Silokek Government Apparatus in managing the Nagari APB for the 2021 fiscal year is the absence of exemplary leadership by the Wali Nagari Silokek in the nagari government organization when managing the Nagari APB for the 2021 fiscal year. There is some evidence, such as, the existence of corrupt practices carried out directly by the Wali Nagari Silokek in managing the Nagari APB, the low level of human resources of the Wali Nagari Silokek, discovered by the Sijunjung Regency Regional Inspectorate Examination Team and the Sijunjung District Prosecutor's Office when carrying out inspections, investigations and investigations. The factors causing corruption by several Nagari Silokek Government Apparatus, in the management of the Nagari Silokek APB for the 2021 fiscal year, namely, the freedom of action and lack of responsibility of the Wali Nagari Silokek, the Secretary of the Nagari Silokek, and the Head of Finance of the Nagari Silokek in the management of the Nagari APB for the 2021 fiscal year. There is several pieces of evidence such as not paying state taxes and regional taxes, fictitious expenses, discovered by the Sijunjung Regency Regional Inspectorate Examination Team. Keywords: Disciplinary Violations, Nagari Government Apparatus, APB Nagari